Expression of Bone Morphogenic Protein in Sinonasal Inverted Papilloma with New Bone Formation - Tomoyo Okamoto M.D.; Satoru Kodama M.D., Ph.D.; Nozomi Nomi M.D., Ph.D.; Shingo Umemoto M.D.; Masashi Suzuki M.D., Ph.D. (Allergy & Rhinology, 2011)
Inverted papilloma (IP) is a common benign tumor in the nose and sinus. Osteogenesis in sinonasal IP is extremely rare; to date, only five cases of IP with new bone formation appear in the literature. In addition, the mechanism of osteogenesis in IP remains unclear. Here, we describe three cases of IP with new bone formation and an investigation into a possible role for bone morphogenic protein (BMP) in osteogenesis. Of three patients with sinonasal IP with new bone formation, two were treated by endoscopic sinus surgery and one was followed up with watchful waiting. Tumor tissues were subjected to immunohistochemistry to detect BMP expression. The patients were successfully treated surgically and showed no evidence of recurrence postoperatively. Follow-up examination is ongoing. Immunohistochemically, the tumors expressed BMP-4 but not BMP-2 or BMP-7. ESS could be successfully used to achieve complete removal of the sinonasal IPs with new bone formation. BMP-4 might be associated with new bone formation in the tumor.